Adsorpsi Isotermal Hidrogen Pada Karbon Aktif Granular Berbahan Dasar Batubara Untuk Aplikasi Penyimpanan Bahan Bakar Pada Teknologi Fuel Cell - Jossy Kolata; Awaludin Martin; Nasruddin Nasruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The limited fossil energy resources and high levels of air pollution led to increased exploration of new and renewable energy sources. Hydrogen has the potential to replace fossil fuels because there is abundant in natural and pollution-free air. The greatest problem in hydrogen is storage methods. Hydrogen storage by adsorption on activated carbon is the best method. Adsorption isotherms of hydrogen on granular activated carbon made from coal with a surface area of 885 m2/g has been implemented by using a volumetric method. Adsorption experiment has been tested at temperature of 45oC and the pressure up to 30 bar. Experiment data in the form of isotherms temperature and variations pressure were calculated to determine the adsorption capacity. Adsorption capacity data were correlated using adsorption isotherms equation of Langmuir and Toth. Adsorption isotherms equation that have result the smallest deviation is the best equation. From the experiment results, the maximum adsorption capacity is 100,91×10-5 kg/kg at isotherm temperature of 45,4°C and a pressure is 29,99 bar. The maximum adsorption capacity occurs at the maximum pressure. Correlation data of adsorption isotherms using the Toth equation has the smallest deviation of 11,73%.Keywords : Adsorption isotherms, volumetric method, adsorption capacity, adsorption isotherms equation.